Batik discharge and discharge-resist printing on lyocell, linen (flax), polyester and polyester/cotton blend fabrics / Muhammad Ismail Ab Kadir - Ab Kadir, Muhammad Ismail (2006)
Batik fabric is printed using physical resist printing method i.e. the use of wax as physical resist agent. Discharge printing is opposite to resist printing. The use of chemical whether as resist or discharge agents to create batik motifs will produce fabrics known as 'fabrics with batik motifs ' i.e. not a true batik according to the definition. The purpose of this research was to produce batiks on ' new' fibers /fabrics of lyocell , linen , polyester and 65/35 polyester/cotton blend fabrics by the application of discharge and discharge-resist printing styles. The techniques used were canting , block and hand screen printing. Discharge printing style was applied on both lyocell , linen , polyester and 65/35 polyester/cotton blend fabrics whilst , discharge-resist printing style was carried out polyester and 65/35 polyester/cotton blend fabrics. The dischargeability of dyestuffs (reactive and disperse) was determined prior to the application of discharge and discharge-resist styles. The fixation methods applied on the printed fabrics were dry heat and ironing. The printed fabrics were then evaluated base on discharge effects and fastness properties to washing , rubbing (crocking), perspiration and light. Tensile strength of unprinted and printed fabrics was also compared. The discharge and discharge-resist styles provide alternative techniques to batik producers in varying their products and designs as well as their method of printing. The ' impossible' to print batik designs on polyester and 65/35 polyester/cotton blends and introduction of new fibers /fabrics of lyocell and linen will create a new market potential for batik producers which can cater different classes of society due to the differences in quality of fibers /fabrics.